Estimating the Genetic Parameters for Calving Score using a Threshold Model, in Charolais Breed - Rodica Stefania Pelmuș; Horia Grosu; Mircea Cătălin Rotar; Mihail Alexandru Gras; Cristina Van (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to determine the breeding value and heritability for calving score using a threshold model for calves from Charolaise breed.  In this study were used records obtained from 2935 calves of Charolais breed from Romanian Breeding Association for Beef cattle. The mean for calving score was 1.35± 0.010. The breeding values for calving score for calves were ranged between -0.2749 and 0.3606. The heritability for calving score was low 0.139. The threshold model was a method of analysis for categorical trait calving score.